Enhancing MSME Competitiveness in Brunei through Halal Certification: Challenges and Training Opportunities - Eva Herianti; Ahmad Yani; Ichwan Arifin; Liza Nora; Amor Marundha; Arna Suryani; Juita Tanjung; Adrian Muluk; Endang Rudiatin; Salahuddin Al Ayubi; Ranisyia dinda alfirani (BASKARA : Journal of Business and Entrepreneurship, 2025)
The International Community Service held in Brunei Darussalam occurred at the Embassy of the Republic of Indonesia in Bandar Seri Begawan, targeting Indonesian micro, small, and medium enterprise (MSME) entrepreneurs residing there. This event was organized in collaboration with the Association of Indonesian Accounting Lecturers (ADAI), the Indonesian Community Association, and the Indonesian Muslim Entrepreneurs Association. The main objective was to unify perspectives on addressing pressing halal issues and enhancing MSME competitiveness through halal certification. Featuring knowledge-sharing sessions themed "Strategies for Enhancing MSME Competitiveness through Halal Certification: Challenges and Opportunities," the event occurred on September 18, 2024, and attracted 150 participants from 40 universities across Indonesia, both online and in person. The implementation method employed a Focus Group Discussion (FGD) approach and in-depth interviews, including training on strategies to improve MSME competitiveness through halal certification, obtaining halal certification, and identifying challenges and opportunities. Activities included preparing the team, introducing topics, summarizing discussions, analyzing data, and assessing the feasibility of qualifying MSMEs. The FGD and training materials cover the halal certification process, benefits, compliance with Islamic law, and strategies to improve MSME competitiveness at the international level and understand the differences in halal certification and product labelling between Indonesia and Brunei.